드론 고도 측정용 FMCW 레이다 신호처리 프로세서 설계 및 구현 - 임의빈; Euibeen Lim; 진소라; Sora Jin; 정용철; Yongchul Jung; 정윤호; Yunho Jung (한국항행학회논문지, 2017)
드론 또는 무인기의 정밀 자세제어를 위해서는 정확한 고도계가 필수적이며, 지상으로부터의 고도측정 정확도로 인해 레이다 고도계가 일반적으로 사용된다. 크기, 무게 및 전력소모 등에 제한으로 인해, 드론에 장착 가능한 레이다 고도계는 PD (pulse Doppler) 방식에 비해 낮은 복잡도를 갖는 FMCW (frequency modulated continuous wave) 방식이 적절하며, 특히, 짧은 송신시간으로 인해 드론 자체 움직임 (ego-motion)에 대응 가능한 fast-ramp FMCW 레이다가 보편적으로 활용된다. 이에, 본 논문에서는 fast-ramp FMCW 레이다 시스템을 위한 드론 고도 측정용 레이다 신호처리 프로세서 (RSP; radar signal processor)의 설계 및 구현 결과를 제시한다. 설계된 RSP는 Verilog-HDL을 이용하여 RTL 설계 후, Altera Cyclone-IV FPGA device를 활용하여 구현 및 검증 되었다. 구현 결과, 총 27,523의 logic elements, 15,798개의 register, 138 Kbits의 memory로 구현 가능하며, 50MHz의 동작주파수로 100Hz의 실시간 고도측정이 가능함이 확인되었다. Accurate altimetry is required for the reliable flight control of drones or unmanned air vehicles (UAVs), and the radar altimeter is commonly used owing to its accuracy for the ground level. Due to the limitation for size, weight and power consumption, the frequency modulated continuous wave (FMCW) radar is appropriate for drone because it has lower complexity than that of pulse Doppler (PD) radar. Especially, fast-ramp FMCW radar, which transmits linear FM signal during very short period, is generally utilized, because it is robust for the ego-motion of drone. Therefore, we present the design and implementation results of the radar signal processor (RSP) for fast-ramp FMCW radar system. The proposed RSP was designed with Verilog-HDL and implemented with Altera Cyclone-IV FPGA device. Implementation results show that the proposed RSP includes 27,523 logic elements, 15,798 registers and memory of 138Kbits and can measure the altimeter at the rate of 100Hz with the operating frequency of 50MHz.